Karolinska Institutet 200-Year Anniversary. Symposium on Traumatic Injuries in the Nervous System: Injuries to the Spinal Cord and Peripheral Nervous System – Injuries and Repair, Pain Problems, Lesions to Brachial Plexus - Sköld, Mattias K.; Svensson, Mikael; Tsao, Jack; Hultgren, Thomas; Landegren, Thomas; Carlstedt, Thomas; Cullheim, Staffan (Frontiers in Neurology, 2011)
The Karolinska Institutet 200 year anniversary symposium on injuries to the spinal cord and peripheral nervous system gathered expertise in the spinal cord, spinal nerve and peripheral nerve injury field spanning from molecular prerequisites for nerve regeneration to clinical methods in nerve repair and rehabilitation. The topics presented at the meeting covered findings on adult neural stem cells that when transplanted to the hypoglossal nucleus in the rat could integrate with its host and promote neuron survival. Studies on vascularization after intraspinal replantation of ventral nerve roots and microarray studies in ventral root replantation as a tool for mapping of biological patterns typical for neuronal regeneration were discussed. Different immune molecules in neurons and glia and their very specific roles in synapse plasticity after injury were presented. Novel strategies in repair of injured peripheral nerves with ethyl-cyanoacrylate adhesive showed functional recovery comparable to that of conventional epineural sutures. Various aspects on surgical techniques which are available to improve function of the limb, once the nerve regeneration after brachial plexus lesions and repair has reached its limit were presented. Mo